Production and Characterization of Monoclonal Antibodies Against Herpes Simplex Virus - Newhook, Lawrence Andrew George (My University, 1980)
Methods for the production of hybrid cell lines (hybridomas) secreting monoclonal antibodies against specific antigenic determinants have recently been developed (Kohler G. and Milstein C., Nature 256, 495, 1975). Monospecific antibodies to Herpes simplex virus (HSV) antigens would greatly facilitate the analysis of HSV type-specific determinants, be of use in molecular studies of virus-cell interactions and could have potential applications in immunization against HSV infections. To this end, spleen cells from HSV2-immunized BALB/c mice have been fused to a BALB/c derived HGPRT myeloma line (Sp 2/0 Ag-14) and the resulting hybrids selected in HAT medium. From 13 successful fusions, 102 hybrid populations secreting antibodies recognizing antigenic determinants specified on HSV2-infected cells have been identified by FITC-immunofluorescence, an ELISA method or a ¹²⁵I-protein A binding assay. Ten of the positive hybrids have been cloned by limited dilutions to generate 124 monoclonal lines reacting specifically with HSV-infected but not with mock-infected cells. High titres of anti-HSV specific antibodies have also been detected in two ascitic fluids recovered from tumors induced in mice by injection of positive hybridomas. Preliminary data on the characterization of two hybridomas in terms of the subclass of immunoglobulins they secrete and the specificities of antibody they define has also been obtained.
Keywords: Medical Sciences; Medical Sciences